Towards institutional fit? The reality of institutional capacity through two food security exemplars. (November 2016) - Slade, Christine; Carter, Jennifer
Highlights: Local government needs alignment with other organizations to address global challenges. Two local government food security exemplars are used to analyse institutional fit. Local government's capacity is constrained by internal lack of fit. There is a simultaneous misalignment between government levels under neoliberalism. Stronger fit requires alignment across government capacity, goals and roles. Abstract: Global challenges face many local governments, which in turn, need to rapidly build their capacity to respond. Local government requires alignment with organizational partners, higher levels of government, external societal actors and local constituents, through the concept of institutional fit, to acquire the capacity to respond to global challenges. Institutional fit discursively enables local government to increase its reach and collective capacity. We analysed institutional fit in two local government case studies in Australia that aimed to improve food security through addressing equity and other social aspects to the challenge. Case study analysis was based on in-depth interviews, primary document analysis and secondary data analysis pertaining to the food security initiatives. Findings show that collaborative partnerships can provide greater understanding of the goals, roles and higher-level commitment needed for institutional fit. Aligning capacities and roles between and within organizations and institutions is also required because local government is severely restricted without whole-of-institutional commitment to similar goals. We found, however, that local government is constrained in its response to change because of the complex nature of the challenge and because neoliberalism militates against fit within the wider domain of the entire institutional response. We argue that institutional fit needs to be embedded within any change process. More nuanced and targeted understandings of the roles of each organization can then be understood, along with the role of power within the institutional domain, so that appropriate planning occurs to identify and target which responses are achieved and by whom.